Graphene-based modulation on the hierarchical growth of Al2O3 heterojunctions outside TiO2 nanofibers via a surfactant-free approach. (October 2020) - Zhan, Qi; Wu, Yanan; Wang, Yunpeng; Liu, Suting; Meng, Xiangyu; Sun, Yueming; Dai, Yunqian
Abstract: Surface engineering of one-dimensional (1D) TiO2 -based heterostructures is extremely vital to the development of new photocatalysts with superior performances. Herein, the Al2 O3 heterojunctions onto TiO2 nanofibers were facilely fabricated by a surfactant-free approach, via employing graphene oxide (GO) sheets as a reliable catalyst of regulating the growth kinetics of heterojunctions. Through adjusting the GO content, the oxygen-containing functional groups of GO provided nucleation sites of Al2 O3 species while restricting their growth in the limited space. As a result, the morphology of Al2 O3 heterojunctions evolved from nanoflakes to nanospikes outside the TiO2 nanofibers that served as robust skeletons. Owing to the distinctive morphology and the effective electron transfer pathway, the photocurrent density of the spiny RGO/Al2 O3 /TiO2 nanofibers was 3.5-times higher than that of pure Al2 O3 /TiO2 nanofibers counterparts toward photoelectrochemical reaction under visible-light irradiation. The present work highlights the pivotal role of graphene sheets in controlling the hierarchical growth of TiO2 -based heterostructures with tunable morphology and compositions. Highlights: A novel Al2 O3 /TiO2  heterostructure was fabricated  via  a surfactant-free approach. The growth kinetics of the Al2 O3 heterojunctions were manipulated by employing graphene oxide sheets as catalysts. The synergistic effect between RGO sheets and the heterostructures promoted the transfer of photogenerated electrons.